2016
DOI: 10.15376/biores.11.3.5854-5869
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Endoglucanase Production by Bacillus aerius on Mixed Lignocellulosic Substrates

Abstract: Selected carbon sources including soluble carboxymethyl cellulose (CMC), insoluble microcrystalline cellulose (MCC), and single (SS)/mixed lignocellulosic substrates (MS), were evaluated for endoglucanase production by B. aerius S5.2. The lignocellulosic substrates of oil palm empty fruit bunch (EFB), oil palm frond (OPF), rice husk (RH), and their mixture (MS) supported growth of the strain better than CMC and MCC. The maximum endoglucanase activity on MS was 7.3-, 2.6-, 1.7-, and 1.2-fold higher than those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…High ethanol yield obtained in the mixture without additional nitrogen supplementation [37] Oil palm and rice residues Endoglucanase production Endoglucanase production was one-to sevenfolds higher on mixed substrate than on single pure cellulosic and lignocellulosic substrates [57] Wheat straw and hybrid poplar Fermentable sugar production…”
Section: Ethanol Productionmentioning
confidence: 99%
“…High ethanol yield obtained in the mixture without additional nitrogen supplementation [37] Oil palm and rice residues Endoglucanase production Endoglucanase production was one-to sevenfolds higher on mixed substrate than on single pure cellulosic and lignocellulosic substrates [57] Wheat straw and hybrid poplar Fermentable sugar production…”
Section: Ethanol Productionmentioning
confidence: 99%
“…As a consequence of the remarkable improvement in enzyme yields by mixture of some lignocellulosic substrates, recent studies have focused on exploiting the synergistic effect of mixing several other substrates to achieve higher yields of hydrolytic enzymes. Rice straw and wheat bran (Shenef et al 2010), OPEFB and rice husk (Oke et al 2016), and several other combinations (Pathak et al 2014) have been mixed, leading to a higher enzyme titre. Given the inductive abilities respectively of simple easily-metabolised sugars (monosaccharides, disaccharides and less complex polysaccharides) and lignocellulosic substrates on xylanase production, it is presumed that the use of a mixture of these respective substrates could lead accordingly to a more efficient xylanase production.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, CMCase (0.21 U/mL) and FPase (0.13 U/mL) activity was recorded by thermophilic Bacillus subtilis BHUJPV-H12 grown on CMC and filter paper substrate (Singh et al 2019). In another study, a lower CMCase activity 0.108 U/mL from B. aureus was observed on MCC (Oke et al 2016). In the current study, better results were found in terms of the enzyme activities.…”
Section: Effect Of Single and Agro-waste Cocktail On Cmcase And Fpase Productionmentioning
confidence: 87%